1999
DOI: 10.1109/84.767114
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the thermal conductivity anisotropy in polyimide films

Abstract: Polymer films are playing an important role in the development of micromachined sensors and actuators, fast logic circuits, and organic optoelectronic devices. The thermal properties of polyimide films govern the temporal response of many micromachined thermomechanical actuators, such as ciliary arrays. This work develops three experimental techniques for measuring both the in-plane and the out-of-plane thermal conductivities of spin-coated polyimide films with thicknesses between 0.5 and 2.5 m, which are comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
86
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(91 citation statements)
references
References 41 publications
4
86
0
Order By: Relevance
“…The solid (black) curve is the TC model with fitting constant k p ¼ 0:68 W=m K, which produces excellent agreement. (The value of k p is not expected to change significantly over the film thickness and temperature ranges used in this study [14].) Similar fits for 1:3 kg=mol PS films can be found in the supplemental section [15].…”
Section: Prl 106 175501 (2011) P H Y S I C a L R E V I E W L E T T Esupporting
confidence: 51%
See 1 more Smart Citation
“…The solid (black) curve is the TC model with fitting constant k p ¼ 0:68 W=m K, which produces excellent agreement. (The value of k p is not expected to change significantly over the film thickness and temperature ranges used in this study [14].) Similar fits for 1:3 kg=mol PS films can be found in the supplemental section [15].…”
Section: Prl 106 175501 (2011) P H Y S I C a L R E V I E W L E T T Esupporting
confidence: 51%
“…Birefringence measurements of spun coat and annealed PS films (150 kg=mol, 2:3 m) have established out-ofplane alignment on oxide coated wafers [16]. Additional studies have shown that the thermal conductivity of polymer microscale films can increase by a factor 4-8 in the direction of alignment [14]. Chain alignment is also observed to increase with decreasing molecular weight and decreasing film thickness [17].…”
Section: Prl 106 175501 (2011) P H Y S I C a L R E V I E W L E T T Ementioning
confidence: 89%
“…The λ value of PPy and polythiophene is 5.0 and 3.8 W/mK, respectively, 20-30 times higher than that of non-conjugated polymers. (b) By directional stretching and external electric or magnetic field [108,109], small molecule monomers can form an orderly arrangement via polymerization, increasing order and crystallinity of the polymers, as well as the free path of phonon propagation, finally to realize high λ value of the polymers. Shen [110] reported a polyethylene (PE) material with ultrahigh λ value of 104 W/mK, ascribed to be stretched into PE fibers with the diameter between 50 and 500 nm, far above that of the original PE matrix, also more than some metals.…”
Section: Fabrication Methods Of Intrinsic Thermally Conductive Polymersmentioning
confidence: 99%
“…The method upon which this work is based involves a micromesa test structure, seen in figure 2 and developed by Kurabayashi, et al (1). The geometry that these mesa structures employ limits the heat path to conduction perpendicular to the surface of the substrate with very little excess heat lost from the sides or top of the structures.…”
Section: Current Testing Methodsmentioning
confidence: 99%